Demanding Work - Francis Green (Princeton University Press, 2013)
No one book, with such a broad canvas, could do more than paint a general picture of the most important workplace changes and to link particular developments with the wider transformations of the international economy. My scope, however, has been especially constrained by the relative scarcity of material for its chosen method. As a result, a preponderance of the discussion in this book concerns Britain, which for many purposes has some of the richest survey-based data series for the study of work life. Elsewhere the book goes where the data are, to say what it can about work-life changes in modern industrialized economies. It is hoped to contribute not only by enhancing understanding of the last quarter century, but also by demonstrating the value of the method, and so stimulating wider and more regular support of high-quality, surveybased research on life at the workplace. If successful, accounts that attempt a similarly wide perspective on workplace change in the next two decades could both be more comprehensive and have a broader geographical scope. For the present, I have largely used whatever goodquality survey series I could find. Doubtless there are and will be more, which can only bode well for the future of research into the quality of work life.